Distracted multinomial model for corona screening at entry ports - Shanmugam, Ramalingam (International Journal of Research in Medical Sciences, 2020)
Background: On 24 January 2020, 1287 corona cases were noticed in Wuhan, China, causing 41 deaths. Its incubation period is at least 14 days. Now, this deadly virus has spread to other foreign countries. The prevalence of corona cases is changing daily. See www.who.org for daily reports. The corona cases are mystic and nightmare to the public, health professionals, and governing agencies globally. Methods: The Center for Disease Control (CDC) compiled in their webpage (www.cdc.org) the number of confirmed, number of healthy, and the number of pending cases at the port of entries in United States of America (USA). These numbers are perhaps under-estimates because of inappropriate diagnostics and imprecise incubation period. To resolve the under estimating, this article, introduces a distracted multinomial model to refine the imprecise corona screening process and interpret the probability of detecting a corona case in US entry gates. Results: An alternate expression (2) for the correlation between the corona ill and corona free cases at the USA ports of entry reveals that it was rising since 31st January 2020, reached its maximum on 5th February 2020, then declined to hit a bottom on 7th February 2020 only to rise again. Conclusions: Most desirable is an accurate predictability of a traveller with the corona virus at the portal entry to minimize its spread. To make such prediction, a regression is necessary with involvement of covariates like age, body’s immunity level, comorbidity, and precise understanding of its incubation period. The model in this article is the starting point for further future research work.